Marjolin ulcer with multifocal origin - Das Sudip; Roy Alok; Maiti Arunasis (Wolters Kluwer Medknow Publications, 2009)
Marjolin ulcer developed from a twenty years old post burn scar. The patient presented with chronic ulceration followed by multifocal development of squamous cell carcinoma with different growth pattern. One nodular lesion grew rapidly to produce a large lesion with history of a little bleeding after trauma but without any pain. Excision followed by skin grafting resulted in good cosmetic scar.